Sanctions and Russian online prices - Jonathan Benchimol; Luigi Palumbo (Journal of Economic Behavior & Organization, 2024)
This study leverages daily web-scraped data to evaluate the impact of economic sanctions following Russia's invasion of Ukraine on consumer prices and product availability across different goods categories. We find that international sanctions significantly disrupted Russian price dynamics, with the exchange rate serving as the primary transmission mechanism. Utilizing granular online data allows us to circumvent potential misreporting and track real-time economic indicators at high frequency. Our analysis uncovers heterogeneous effects across product groups, with sanctions associated with an average increase of 11.7 percentage points in the Russian CPI. The results highlight how trade policies and geopolitical events can rapidly propagate through retail markets, underscoring the importance of timely price monitoring during periods of economic turbulence. More broadly, we demonstrate the value of online data for evaluating policy shocks, paving the way for similar applications in other contexts.
Keywords: E21; E31; F13; F38; F51; D74; P16; C81; 330; Political economy; Online prices; Product availability; Sanctions; Conflict; Russia; Ukraine; War; Big data; Russo-Ukrainian war; Product prices